Integrated Guided Inquiry Learning Model of Ethnochemistry on High School Students' Critical Thinking Skills and Learning Interest in Reaction Rate Material - Hana' Fadhilah Retiyanto; Nurfina Aznam; Muhammad Habib Ash Shiddiqi; Febri Nurason (Yayasan Keluarga Guru Mandiri, 2025)
This study investigates the effect of the guided inquiry learning model integrated with ethnochemistry on senior high school students' critical thinking skills and learning interest in reaction rate. A quasi-experimental design with a pretest-posttest control group was employed, involving 60 students of class XI MIPA at SMAN 4 Lubuklinggau, selected through random sampling. Data were collected using a critical thinking test and a learning interest questionnaire, and analyzed with MANOVA. Findings revealed significant differences in critical thinking and learning interest between the two groups, with effective contributions of 65.7% simultaneously, 43.2% individually to critical thinking, and 44.3% to learning interest. These results demonstrate that guided inquiry integrated with ethnochemistry not only enhances students' cognitive and affective outcomes but also contributes to science education by contextualizing learning through local culture. It is therefore suggested that this model be applied to other chemistry topics and across broader student populations to strengthen its effectiveness and further enrich culturally grounded science learning.